The determinants of foreign direct investment in Malaysia / Nur Nadiah Abu Bakar (Faculty of Business and Management, 2007)
This research report aims to identify the determinants of foreign direct investment (FDI) in Malaysia. In 2005, Malaysia's inward FDI dipped 14 percent to US$3.97bil, the only Asean country to register a decline. Empirical studies overseas have shown that economic, social and political factors are important determinants of FDI inflows. It cannot be very much different in the case of Malaysia. Inflows of FDI in Malaysia always fluctuate over the years. The fluctuations are because of the Asian financial crisis in 1997, increasing number in world oil price and the emerging markets like China and lndia. The research objectives are to study the trend of FDI inflows and the factors that influence the FDI inflows to Malaysia. In this study, researcher has used secondary data. The data used in this study covers annual data for the period from 1976 until 2005. In addition, researcher used multiple regression analysis in this study because the independent variables are more than two. The fluctuation of FDI inflows in Malaysia can be seen in data analysis section. From the regression analysis, all of the independent variables show the correct theoretical signs and significant except for inflation rate.